Translational phases of evidence in a prognostic biomarker: a systematic review and meta-analysis of natriuretic peptides and the prognosis of stable coronary disease. Issue 8 (3rd March 2012) - Sutaria, Shailen; Philipson, Peter; Fitzpatrick, Natalie K; Abrams, Keith; Moreno, Santiago G; Timmis, Adam; Hingorani, Aroon D; Hemingway, Harry
Abstract : Context: Translational phases of study are important in evaluating whether a prognostic biomarker is likely to have impact on clinical practice but systematic evaluations of such evidence are lacking. Objective: To systematically evaluate the clinical usefulness of the published literature on the association of natriuretic peptides (NP) and prognosis in stable coronary disease. Data sources: MEDLINE and EMBASE until the end of July 2009, without restrictions. Study selection: Prospective studies measuring NP in people with stable coronary disease who were followed-up for all cause mortality, coronary or cardiovascular events. Data extraction: Two independent reviewers categorised studies according to the American Heart Association phase of study, and extracted data according to the study reporting guidelines from the American Heart Association and REMARK. Results: Systematic review of 19 studies found 17 which were phase 2, reporting an association between NP and events, two phase 3 studies, statistically examining the incremental prognostic value of NP, but no studies assessing whether NP predicted risk sufficiently to change management (phase 4), improve clinical outcomes (phase 5) or cost effectiveness (phase 6). No study referred to a statistical analytic protocol. Meta-analysis of 14 studies, reporting 18 841 patients and 1655 outcome events, found an RR for events of 3.28 (95% CI 2.45 to 4.38) comparing top versus bottom third of NP. This effect was 26% lower among the five studies which adjusted for a priori confounders (age, sex, renal function and left ventricular function) and 38% lower when adjusting for publication bias (Egger's p=0.001). Conclusion: The unbiased strength of association of NP with prognosis in stable coronary disease is unclear, and there is a lack of reports of clinically useful measures of prediction and discrimination or studies relating NP levels to clinical decision making. The available literature is confined to early phases and is of limited clinical usefulness.